Organic Food Brand Trust and Brand Loyalty: Evidence from Thailand - Pattweekongka, Supawadee (My University, 2022)
This study investigates the antecedents of trust in organic food brands and the effect of brand trust on brand loyalty. Previous research has addressed brand trust, but none has examined brand trust concerning brand loyalty in organic goods, a developing trend in many nations. A survey was done with 386 Thai consumers of organic foods. Using path analysis, the magnitude and relationships between variables were estimated. The findings indicate that brand competency and generosity increase organic brand trust. Moreover, brand trust was found to influence both attitudes and behaviors about brand loyalty. The study predicts that brand trust inspired 76% of the purchasing behavior loyalty
Keywords: Brand benevolence; Brand competency; Brand credibility; Brand loyalty; Brand trust; Organic food